Serum IP-10 and IL-7 levels are associated with disease severity of coronavirus disease 2019. (June 2021) - Wang, Guo-Lin; Gao, Hui-Xia; Wang, Yu-Ling; Wei, Xiao; Liu, Yu-Zhen; Lu, Jian-Hua; Li, Li; Wang, Hai-Bin; Zhao, Lei; Rong, Yan-Xiao; Yao, Lin; Duan, Li-Juan; et al.
Abstract: We quantified the serum levels of 34 cytokines/chemokines in 30 patients with SARS-CoV-2 infection. Elevated levels of IP-10 and IL-7 were detected in the acute and convalescent stages of the infection and were highly associated with disease severity.